Immune cells at the feto-maternal interface: Comprehensive characterization and insights into term labor - Mosebarger, Angela; Vidal, Manuel S.; Bento, Giovana Fernanda Cosi [UNESP]; Lintao, Ryan C.V.; Severino, Mary Elise L.; kumar Kammala, Ananth; Menon, Ramkumar (Elsevier, 2024)
Immune cells at the feto-maternal interface play an important role in pregnancy; starting at implantation, maintenance of pregnancy, and parturition. The role of decidual immune cells in induction of labor still needs to be understood. Published reports on this topic show heterogeneity in methods of cell isolation, assay, analysis and cellular characterization making it difficult to collate available information in order to understand the contribution of immune cells at term leading to parturition. In the present study, available literature was reviewed to study the differences in immune cells between the decidua basalis and decidua parietalis, as well as between immune cells in term and preterm labor. Additionally, immune cells at the decidua parietalis were isolated from term not in labor (TNL) or term in labor (TL) samples and characterized via flow cytometry using a comprehensive, high-dimensional antibody panel. This allowed a full view of immune cell differences without combining multiple studies, which must include variation in isolation and analysis methods, for more conclusive data. The ratio of cells found in decidua parietalis in this study generally matched those reported in the literature, although we report a lower percentage of natural killer (NK) cells at term. We report that CD4 expression on CD8- NK cells decreased in term labor compared to not in labor samples, suggesting that natural killer cells may be migrating to other sites during labor. Also, we report a decrease in CD38 expression on CD8+ CD57+ T cells in labor, indicative of cytotoxic T cell senescence. Our study provides a comprehensive status of immune cells at the decidua-chorion interface at term.
Keywords: CD45 cells; Flow cytometry; Immunity; NK cells; Pregnancy; T cells